Hand-arm vibration of unskilled oil palm motorised cutter operator - Md Salleh, Salihatun; Rahim, E.A.; Roslan, Mohd Nazrul; Ismon, Maznan; Madlan, M.A.; Masrol, Shaiful Rizal; Jelani, Abdul Razak; Ahmad, Mohd Rizal (Trans Tech Publications, 2013)
The portable petrol driven oil palm motorised cutter or CANTAS has been identified as a type of machine that generates hand-arm vibration. These vibrations can cause complex vascular, neurological and musculoskeletal disorder known as hand-arm vibration syndrome (HAVS) when over exposure of daily usage. The objective of this study is to investigate the vibration level at different angles during the operational of the CANTAS including idle and full throttle conditions. The CANTAS vibration experiments were carried out at a farm in Parit Raja, Batu Pahat, Johor. A student participated as the unskilled worker and was assisted by two technical staffs to conduct the vibration measurements. The measurement was taken during the operations of cutting first fronds, second fronds and a fruit bunch during idle and full throttle conditions and by varying the inclination angle. The inclinations of cutting angle were varied from 45º, 60º and 75º. The hand-arm vibration value, ahv achieved 10.93 ±1.2 m/s2 and 7.94 ± 1.0 m/s2 for unskilled user during operation of two bunches and one pruning frond for all angles at point 1 and point 2 handle respectively. Mean vibration values at both point of handles resulted in vibration values of 10.12±3.8m/s2 at 450, 9.15±3.0m/s2 at 600 and 9.03±1.8m/s2 at 750. Increasing the angle overall results in decreasing the level of vibration at both handle points.